Increased SARS-CoV-2 seroprevalence and spread of infection without awareness among healthcare workers through 2020–2022 in a Japanese medical center - Rie Kanamori; Yan Yan; Kanami Ito; Hiroshi Fukuda; Satoshi Hori; Takamasa Yamamoto; Gene Igawa; Kaori Saito; Yuki Horiuchi; Shuko Nojiri; Yuji Nishizaki; Yoko Tabe; et al. (Scientific Reports, 2023)
Abstract Despite Japan’s high vaccination coverage, daily numbers of new COVID-19 cases have been high. However, studies on the seroprevalence among Japanese people and the causative factors for rapid spread have remained limited. In this study, we aimed to examine the seroprevalence and associated factors in healthcare workers (HCWs) of a medical center in Tokyo using blood samples drawn at annual check-ups from 2020 to 2022. We found that of the 3,788 HCWs in 2022 (by mid-June), 669 were seropositive for N-specific antibodies (tested by Roche Elecsys Anti-SARS-CoV-2 assay); the seroprevalence surged from 0.3% in 2020 and 1.6% in 2021 to 17.7% in 2022. Notably, our study found 325 (48.6%; 325/669) cases were infected without awareness. Among those with a previously PCR-confirmed SARS-CoV-2 infection during the past three years, 79.0% (282/357) were found after January 2022, after the Omicron variant was first detected in Tokyo at the end of 2021. This study indicates the fast spread of the SARS-CoV-2 among HCWs during the Omicron surge in Japan. The high percentage of infection without awareness may be a key driving factor causing rapid person-to-person transmission, as shown in this medical center with high vaccination coverage and strict infection control measures.